THE MEDIATING INFLUENCE OF DEMOGRAPHIC FACTORS ON THE PURCHASE INTENTION OF ORGANIC FOOD AMONG ACADEMIC STAFF OF NIGERIAN UNIVERSITIES. (Journal of the Management Sciences, 2024)
This research concerns the mediating influence of demographic factors on the purchase intention of organic food among academic staff of Nigerian universities. Employing a quantitative research methodology, this research collected data through structured questionnaire distributed to a sample of 370 academic staff members across various universities in south-east, Nigeria, achieving a response rate of 82.16% with 304 valid responses. The research hypotheses were tested using statistical methods to assess direct and indirect effects, with a significance threshold set at the 5% level. Our analysis revealed several key findings. Firstly, there was a strong direct effect of attitudes towards organic food benefits on purchase intentions, with a coefficient of 0.6764 and a 95% confidence interval ranging from 0.6020 to 0.7509, indicating a robust positive influence. Furthermore, demographic factors were found to mediate this relationship significantly, as evidenced by an indirect effect of 0.0230 with a bootstrap confidence interval not including zero (0.0067 to 0.0461). Similarly, motivations for purchasing organic food displayed a direct negative impact on purchase intentions (coefficient -0.3857, 95% confidence interval from -0.4870 to -0.2843) and were also significantly mediated by demographic factors, showing an indirect effect of -0.0403. The study also established the significant influence of subjective norms and awareness and information sources on purchase intentions, with respective coefficients of 0.2726 and -0.3492. In both cases, demographic factors served as a significant mediator, enhancing our understanding of how individual characteristics intersect with cultural and social influences to affect behavioural outcomes in organic food markets. Barriers and challenges related to sourcing organic food emerged as another critical factor positively influencing purchase intentions, demonstrated by a direct effect coefficient of 0.3485 and confirmed mediation by demographic factors (indirect effect 0.0485). This finding suggests that overcoming such barriers may significantly boost organic food consumption among this demographic. These findings underscore the necessity for targeted educational campaigns and institutional support to navigate the identified barriers effectively and foster a more sustainable consumption pattern among academics.
Keywords: Demographic Factors, Organic Food Benefits, Purchase Intentions, Subjective Norms, Barriers and Challenges, Awareness and Information Sources.